159 Vascular Regeneration is Impaired in the Setting of Systemic Insulin Resistance. (31st May 2014) - Cubbon, Richard; Aziz, Amir; Mercer, Ben; Yuldasheva, Nadira; Skromna, Anna; Makava, Natalia; Sengupta, Anshuman; Ali, Noman; Walker, Andrew; Gatenby, Victoria; Wheatcroft, Stephen; Kearny, Mark; et al.
Abstract : Introduction: An increase in cardiovascular disorders is responsible for much of the premature mortality seen in patients with type 2 Diabetes Mellitus (DM). Importantly, insulin resistance or 'pre-diabetes', is also associated with an increased risk of cardiovascular events and mortality. Therapeutic manipulation of endogenous vascular regeneration is an attractive goal in the management of ischaemic disorders in these patients. A large body of evidence shows that DM is associated with diminished vascular regeneration; however, the mechanistic contribution of insulin resistance per se is not well established. Methods: The insulin receptor knockout mouse (IRKO) is haploinsufficient for the insulin receptor, resulting in mild metabolic insulin resistance, but without hyperglycaemia. Vascular regeneration was assessed using a murine model of critical limb ischaemia in male IRKO mice, versus wild-type (WT) littermates controls (n = 10 per group). Limb perfusion was assessed serially at days 0, 7, 14 and 21 using laser Doppler analysis. Expression of VEGF-A in the ischaemic limb muscle was assessed using qRT-PCR in a further group of mice 3 days after induction of ischaemia. Angiogenesis was assessed ex vivo in an aortic sprouting assay, and in vitro using VEGF-A induced murine pulmonary endothelial cell (PEC) vascular network formation on Matrigel. Data is expressed as mean [SEM]; p < 0.05 is denoted by *. Results: IRKO mice had delayed recovery in limb perfusion in comparison to (WT) mice, with a reduction in the ischaemic/non-ischaemic flux ratio observed at day 7 (WT 47.0[3.5] vs. 36.4 [3.5]%*), day 14 (WT 84.8[5.4] vs IRKO 63.4[5.5]%*) and day 21 (WT 89.3[6.3] vs IRKO 68.9[8.2]%, p = 00.06). Quantitative RT-PCR revealed a 3.2 fold greater* expression of VEGF-A in the ischaemic adductor muscle of IRKO versus WT mice. Endothelial sprouts from the aortae of WT mice were more abundant, and were longer, than those seen from IRKO aortae when stimulated with VEGF (WT 29.93[2.19] vs IRKO 21.82[2.42] endothelial sprouts *) and (WT 1037.46[38.58] vs IRKO 846.51[37.98] µm*). WT PECs produced significantly more vascular tubules in response to VEGF than IRKO PECs (WT 27.5[2.9] vs IRKO 14.3[2.4] tubular structures/microscopic field *). Conclusion: These data are the first to demonstrate that ischaemia-associated vascular regeneration is impaired in the setting of global insulin receptor haploinsufficiency. This finding is complemented by in vitro data demonstrating impaired indices of angiogenesis in the IRKO mouse. Moreover, our work provides hints that insulin resistance is associated with functional VEGF resistance, which may be relevant to defining therapeutic targets in future studies.